Polymer design for solar cell – Current trend and future scenario. (November 2015) - Hemavathi, B.; Ahipa, T.N.; Pai, Ranjith Krishna
Graphical abstract: Highlights: The aspects of different designs for polymer solar cell were discussed. Present designs and future scenario are included in the review. Polymer structure and their PCE were tabulated. Eight different building blocks were discussed separately along with copolymers. Abstract: Polymer molecular design is a crucial aspect for fabricating a better polymer solar cell with enhanced efficiency. In this review, we discussed the various polymeric designs (P1–172 ) encompassed of electron rich donor and electron deficient acceptor moieties in the main chain as well as in the side chain to facilitate effective intra-molecular charge transfer. Further, the application of these polymeric materials influenced significantly on the PCE of polymeric solar cells. So far, PCE of 7–8% were reported for these polymeric materials along with the fullerene derivatives. Along with improved efficiency for the polymer solar cell (PSC), other desirable parameters were also considered like, easy processibility, broad absorption range, low band gap and improved thermal/device stability of the polymers. In this review, we have discussed the current trend in the polymer design to improve the power conversion efficiency and suggest a possible scenario for the future development in the polymer design.